Antibiotic Susceptibility of MRSA Isolates at Idlib University Hospital Using the Vitek-2 System - Bkhsow, Amr Alkheer Ebrahim; Al-Daoud, Fouad Hamad (Journal of medical and pharmaceutical sciences, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is recognized as one of the most significant causes of hospital-acquired infections due to its high ability to acquire multidrug resistance, posing a major challenge to infection control. Objective: This study aimed to determine the prevalence of MRSA at Idlib University Hospital and evaluate its susceptibility to antibiotics and disinfectants. Methods: A total of 136 samples were collected from patients, healthcare staff, surfaces, and air in intensive care units, operating rooms, and hospital wards between June 15, 2023, and June 15, 2024. After excluding 11 duplicate samples, 125 valid, non-duplicate samples were analyzed. Samples were cultured on modified chromogenic agar containing cefoxitin, and identification was performed using the Vitek-2 system with the GP card. Antibiotic susceptibility testing was conducted using the AST-P664 card, and disinfectant susceptibility was assessed by the disk diffusion method. Results: MRSA prevalence was 17.6% (22/125), distributed among patients (36.36%), healthcare staff (12.9%), and air samples (40%), with higher prevalence in males (50%) compared to females (30%). Isolates exhibited complete resistance to penicillin and methicillin (100%), high resistance to cefoxitin (75%), clindamycin and erythromycin (85%), oxacillin (70%), and fusidic acid (45%), while remaining fully susceptible (100%) to tigecycline, nitrofurantoin, and mupirocin. Regarding disinfectants, all isolates showed complete resistance (100%) to ethanol, high resistance to Cidex, and moderate susceptibility to povidone-iodine. Conclusions and Recommendations: MRSA is prevalent at Idlib University Hospital and exhibits multidrug resistance. Strict infection control measures should be implemented, physicians should perform identification and susceptibility testing before prescribing antibiotics, and disinfectant efficacy should be regularly monitored.
Keywords: Hospital-acquired infections; antimicrobial resistance; multidrug resistance; disinfectant resistance; methicillin-resistant Staphylococcus aureus (MRSA); Vitek-2 system; Idlib University Hospital